Why creating standardized core outcome sets for chronic kidney disease will improve clinical practice. Issue 8 (23rd October 2015) - Nistor, Ionut; Bolignano, Davide; Haller, Maria C.; Nagler, Evi; van der Veer, Sabine N.; Jager, Kitty; Covic, Adrian; Webster, Angela; Van Biesen, Wim
Abstract: Chronic kidney disease (CKD) is common and is associated with increased mortality, morbidity and cost. However, insufficient high-quality trial data are available to answer many relevant clinical questions in this field. In addition, a wide range of variable outcomes are used in studies, and often they are incompletely reported. Furthermore, there is a lack of patient-relevant outcomes, such as mortality, morbidity, quality of life, pain, need for dialysis or costs. Common problems with outcome reporting are as follows: choosing the wrong domains to measure; within domains, choosing the wrong measures (invalid surrogates, composite, non-patient relevant); within measures, choosing the wrong/variable metrics; and within metrics, choosing variable presentation methods. With this article, we aim to underline why standardized outcome reporting is key to achieving evidence-based guidance and improving clinical care for patients; highlight the frameworks available for achieving core outcome sets; and starting from these frameworks, we propose steps needed to develop a core outcome set in the field of CKD. We hope that standardized core outcome sets for nephrology will lead to the most important outcome of guideline production, improving outcomes for our patients.